2017
DOI: 10.1002/adem.201700747
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Diamond Tools for Dental Ceramics Processing

Abstract: This paper is focused on preparing diamond tools with orderly arranged abrasive particles for dental ceramics processing via 3D printing. This allows one to overcome such drawbacks of the existing methods of dental ceramics processing as weak bonding strength, short service life, and irregular diamond distribution in diamond tools. Firstly, the CAD model of the dental diamond tool is constructed using 3D cartographic software, with level-scanpath geometry information generated via hierarchcal slicing. Then, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Currently, mainly AM powder methods with metals and their alloys are used to build fully functional and responsible mechanical parts. Elements of this type are used in the aerospace, offshore, and energy sectors [ 36 , 74 , 75 ] as well as in the automotive, electronics, medical [ 76 , 77 ] and tool industries [ 78 , 79 ], among others.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…Currently, mainly AM powder methods with metals and their alloys are used to build fully functional and responsible mechanical parts. Elements of this type are used in the aerospace, offshore, and energy sectors [ 36 , 74 , 75 ] as well as in the automotive, electronics, medical [ 76 , 77 ] and tool industries [ 78 , 79 ], among others.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…However, diamond is difficult to be machined, so it's expected to use 3D printing for diamond material development to get parts with superior properties and flexible configurations. Yang et al [1] used selective laser sintering (SLS) to inlay 300-500 μm diamond particles regularly on Ni-Cr alloy and fabricated metal-bonded diamond grinding wheels with superior grinding performance. Fox et al [2] prepared diamond-Ti composites with great potential for medical implant applications through laser metal deposition (LMD).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the diamond grits did not fall off, even after the grinding processes involving a heavy load. In addition, in 2017 Yang tentatively manufactured a multilayer diamond tool via 3D printing technology [23]. First, the diamond grits were randomly sprayed onto alloy powders and sintered by a laser beam, according to the design requirements; the diamond grits that were not sintered were wiped away using a sparger.…”
Section: Introductionmentioning
confidence: 99%